Pathophysiology of Myocardial Infarction With Nonobstructive Coronary Artery Disease: A Contemporary Systematic Review - Laurie-Anne Boivin-Proulx, MD, MSc; Kevin Haddad, MD, MSc; Marco Lombardi, MD; Aun Yeong Chong, MD; Javier Escaned, MD, PHD; Swati Mukherjee, MD; Jessica Forcillo, MD, PhD; Brian J. Potter, MDCM, SM; Thais Coutinho, MD; Christine Pacheco, MD, MSc (CJC Open, 2024)
Background: Myocardial infarction with nonobstructive coronary artery disease (MINOCA) is defined as acute myocardial infarction (AMI) with angiographically nonobstructive coronary artery disease. MINOCA represents 6% of all AMI cases and is associated with increased mortality and morbidity. However, the wide array of pathophysiological factors and causes associated with MINOCA presents a diagnostic conundrum. Therefore, we conducted a contemporary systematic review of the pathophysiology of MINOCA. Methods: A comprehensive systematic review of MINOCA was carried out through the utilization of the PubMed database. All systematic reviews, meta-analyses, randomized controlled trials, and cohort studies available in English or French that reported on the pathophysiology of MINOCA published after January 1, 2013 were retained. Results: Of the 600 identified records, 80 records were retained. Central to the concept of MINOCA is the definition of AMI, characterized by the presence of myocardial damage reflected by elevated cardiac biomarkers in the setting of acute myocardial ischemia. As a result, a structured approach should be adopted to thoroughly assess and address clinically overlooked obstructive coronary artery disease, and cardiac and extracardiac mechanisms of myocyte injury. Once these options have been ruled out, a diagnosis of MINOCA can be established, and the appropriate multimodal assessment can be conducted to determine its specific underlying cause (plaque disruption, epicardial coronary vasospasm, coronary microvascular dysfunction, and coronary embolism and/or spontaneous coronary dissection or supply-demand mismatch). Conclusions: Integrating a suitable definition of AMI and understanding the pathophysiological mechanisms of MINOCA are crucial to ensure an effective multimodal diagnostic evaluation and the provision of adequate tailored therapies. RÉsumÉ: Contexte: L’infarctus du myocarde sans obstruction des artères coronaires (MINOCA) est défini comme un infarctus aigu du myocarde (IAM) en présence d’une coronaropathie non obstructive confirmée par angiographie. Le MINOCA représente 6 % de tous les cas d’IAM et est associé à une hausse des taux de mortalité et de morbidité. Cependant, le large éventail de facteurs physiopathologiques et de causes associés au MINOCA représente une énigme diagnostique. C’est pourquoi nous avons réalisé une analyse systématique des publications contemporaines sur la physiopathologie du MINOCA. Méthodologie: Une analyse exhaustive des publications sur le MINOCA a été menée au moyen de la base de données PubMed. L’ensemble des analyses systématiques, des méta-analyses, des essais contrôlés randomisés et des études de cohorte publiés en anglais ou en français après le 1er janvier 2013 qui faisaient état de la physiopathologie du MINOCA ont été retenus. Résultats: Parmi les 600 dossiers relevés, 80 ont été retenus. La définition de l’IAM était centrale au concept de MINOCA et était caractérisée par la présence d’une lésion myocardique attestée par des taux élevés de biomarqueurs cardiaques en contexte d’ischémie myocardique aiguë. Par conséquent, une approche structurée devrait être adoptée pour évaluer pleinement et traiter les coronaropathies obstructives qui passent inaperçues en clinique ainsi que les mécanismes cardiaques et extracardiaques des lésions aux myocytes. Une fois ces options exclues, un diagnostic de MINOCA peut être établi et l’évaluation multimodale appropriée peut être menée pour déterminer la cause sous-jacente précise (rupture de plaque, vasospasme d’une artère coronaire épicardique, dysfonction microvasculaire coronarienne et embolie coronarienne et/ou dissection spontanée d’une artère coronaire ou déséquilibre entre apports et besoins). Conclusions: Il est crucial d’intégrer une définition convenable de l’IAM et de comprendre les mécanismes physiopathologiques du MINOCA pour assurer une évaluation diagnostique multimodale efficace et une prestation de traitements adaptés et adéquats.